(untitled) (International Journal of Current Engineering and Technology, 2015)
In recent years, many routing protocols have been proposed to improve the lifetime, energy efficiency, deployment of nodes, latency, fault tolerance, robustness, and reliability of Wireless Sensor Networks (WSN). The energy constraints and prolonging the lifetime of the WSN is very important role of routing protocols. Different cluster based routing protocol have proposed to improve the conventional protocols i.e. direct transmission, multi-hop routing, static clustering and minimum-transmission-energy. Among all cluster based protocols, Low-Energy Adaptive Clustering Hierarchy (LEACH) is the most prominent WSN protocol. In this project, we have tried to expand the LEACH by adding different features in LEACH for homogeneous and heterogeneous environments. We have proposed SEA LEACH (Special energy advanced node) by introducing proficient cluster head selection scheme and different transmitting power levels for LEACH in homogeneous environment. But, energy saving scheme of homogeneous environment is not suitable for heterogeneous environment. Stable Election Protocol (SEP) is the dynamic heterogeneous routing protocol. SEP is based on weighted election probabilities of each node to become the cluster head according to the remaining energy in each node. We propose advanced node LEACH by applying different ways of communication (between CH to sink) for advanced and normal nodes. By showing simulation, we prove that advanced node LEACH is more energy efficient and has longer lifetime of network than LEACH in homogeneous and heterogeneous environments.